Concordance and complementarity in IP instruments - Marco Grazzi; Chiara Piccardo; Cecilia Vergari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
This work investigates the relationship between proxies of innovation activities, such as patents and trademarks, and firm performance in terms of revenues, growth and profitability. By resorting to the virtual universe of Italian manufacturing firms this work provides a rather complete picture of the Intellectual Property (IP) strategies pursued by Italian firms, in terms of patents and trademarks, and we study whether the two instruments for protecting IP exhibit complementarity or substitutability. In addition, and to our knowledge novel, we propose a measure of concordance (or proximity) between the patents and trademarks owned by the same firm and we then investigate whether such concordance exert any effect on performance.
Keywords: O31; O34; L25; 330; Trademarks; Patents; Innovation; Intellectual Property; Complementarity; Concordance; Technological proximity; firm performance; firm growth